Surgical tactics for acute abdominal complications of primary hyperparathyroidism. Clinical case - Viсtor P. Morozov; Marina E. Boriskova; Mikhail A. Bykov; Elena S. Did-Zurabova; Dmitrii V. Kulikov; Elmira A. Ramazanova; Bibigul R. Kelbetova (ZAO "Consilium Medicum", 2021)
Primary hyperparathyroidism (PH) is one of the most common diseases of the endocrine system that requires surgical treatment. The most common cause of PH is parathyroid adenoma, which occurs in 8590% of cases, in 510% multiple adenomas or hyperplasia of several or all parathyroid glands. Surgical treatment is the only radical and effective method of treating PH, however, the variability of the anatomy of the parathyroid glands, the possibility of their ectopic location, as well as the close connection with the thyroid gland, in some cases, complicate the intraoperative verification of the parathyroid adenoma. All this can lead to inadequate volumes with parathyroidectomy. In this article, the presented clinical case demonstrates how the complexity of intraoperative verification of the parathyroid glands during parathyroidectomy led to intra-abdominal life-threatening complications acute duodenal ulcer with subsequent perforation and acute cholecystitis against the background of persistent hypercalcemia and perioperative stress. Also, on the example of this case, surgical tactics are demonstrated, taking into account the pathogenesis of abdominal complications.